Peran Perempuan Amerika dalam Agama - Juliasih Kusharyanto; Siti Chamamah- Soeratno; Stephanus Djawanai (Humaniora, 2004)
Education for women, which is at first intended to transform them to be good mothers in raising their children, especially in providing basic education of religion for them, has become a boomerang. Religion and education transform women into religious and intellectual figures. They start to realize and think of their existence. They are different from men only physically, but it does not necessarily mean that they are also intellectually different. They prove themselves that they are able to develop their intellectuality if there is the opportunity. They become women who are thinking, confident, brave, and self-sufficient. Their role and activities in religion show their potency.